Study of the Heat Shock Protein 70 Polymorphism on Thermotolerance in Kankrej Cattle - Chaudhary, Dhavalkumar F; Kharadi, Vishnu B; Ramani, Umed V; Janmeda, Mamta; Baravaleeya, Krutiben; Koladiya , Hirali (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Heat shock protein (HSP) 70 is a key player in the development of thermotolerance among the several members of the HSP superfamily,  which function as a molecular chaperon by attaching to denaturing proteins and stabilising them while maintaining their activity.  The current study intended to screen the HSP70 gene in cattle of the Kankrej breed for polymorphisms and potential variations in  thermotolerance. A 295 bp fragment of HSP70 gene was subjected to PCR - Single Strand Conformation Polymorphism (SSCP) in 100  Kankrej cattle. Association of thermolerance traits, viz., rectal temperature, respiration rate and pulse rate with identified genotypes were  analyzed for different seasons. Three SSCP patterns, viz., AA, AB and BB and consequently two alleles namely A and B were documented in  fragment of HSP70 gene. Comparative association of identified genotypes with different heat tolerance traits were found non-significant.  However, it is anticipated that the polymorphism at HSP70 may be a strong predictor of cow heat tolerance, which could help with  thermotolerance selection screening large number of samples and future genetic improvement in breeding.
Keywords: HSP 70 polymorphism; Kankrej cattle; SSCP; Thermo-tolerance traits